Optimization of estimates of electrophysical parameters and statistical characteristics of spatially-distributed objects in the wideband aperture synthesis systems - Volosyuk, V.K.; Zhyla, S.S.; Pavlikov, V.V. (Radiotekhnika, 2017)
Using the criterion of the maximum of the likelihood functional, an optimal algorithm for processing noise processes of radiothermal radiation of spatially extended objects in multichannel radiometric systems of aperture synthesis is synthesized. A special feature of the solved problem is the use of VF spectral transformations that do not require quasimonochromatic approximation and allow solving the synthesis problem of the processing algorithm for broadband and ultra-wideband processes. A number of simplifications of the obtained algorithm for the development of quasioptimal aperture synthesis systems are proposed.